1981
DOI: 10.7567/jjaps.20s4.201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Growth and Characterization of ZnO Single Crystals

Abstract: Large flawless crystals of ZnO up to 25×10×5 mm3 in size have been grown hydrothermally in a specially designed autoclave. Difficulties on the hydrothermal growth of ZnO single crystals were almost surmouted by in situ determination of solution temperatures under operating conditions. The characteristics of the growth crystals are discussed on the basis of the correlation with growth conditions, and it is found that a nonstoichiometry in the grown ZnO is enhanced with being apt to involve O vacancies due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The oxygen pressure used during the growth process for the epilayers is 10 −5 torr (sample A), 10 −4 torr (B) and 10 −3 torr (C), which tunes the carrier concentration. Sample D (commercial single crystal from Tokyo-Denpa Company Ltd. grown by hydrothermal method 12 ) is mounted on fused silica and polished down to a few microns for transmission measurements.…”
mentioning
confidence: 99%
“…The oxygen pressure used during the growth process for the epilayers is 10 −5 torr (sample A), 10 −4 torr (B) and 10 −3 torr (C), which tunes the carrier concentration. Sample D (commercial single crystal from Tokyo-Denpa Company Ltd. grown by hydrothermal method 12 ) is mounted on fused silica and polished down to a few microns for transmission measurements.…”
mentioning
confidence: 99%
“…Zinc acetate dihydrate (98%, Aldrich) was dissolved in about 50 g of deionized, degassed water. A series of syntheses were done with only hydroxide as a ligand, for zinc molalities ranging from 0.038 to 0.061, pH 14 and at least 4 molar equivalents of KOH (85+%, Aldrich) added to each pretreated sample to enable formation of Zn(OH) 4 2À . To all other solutions, one molar equivalent of one of the following reagents was added: ethylenediaminetetraacetic acid (99.5%, Aldrich), ethylenediaminetetraacetic acid disodium salt dihydrate (99+%, Aldrich), diethylenetriaminepentaacetic acid (DTPA) (97%, Aldrich) and tetraethylenepentamine pentahydrochloride (98%, Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, hydrothermal synthesis of crystals requires the addition of lithium hydroxide as a mineralizer, which compromises the electrical properties of the product [3,4]. Thus, the prospect of synthesizing high-quality crystals without the need for lithium is worth pursuing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value was at the level or lower the level of the concentration of most metallic impurities. A nonstoichiometry in the grown ZnO is enhanced due to a reductive atmosphere under hydrothermal conditions [32]. The dependence of defect formation on the annealing in O 2 and N 2 atmospheres showed that below 850 0 C, Zn interstitials become the dominated point defects but for the ZnO films annealed at higher temperatures, oxygen vacancies become the predominant defects [33].…”
mentioning
confidence: 99%